Promotion of Renewable Energy in the EU and Ukraine (Kyiv-Mohyla Law and Politics Journal, 2021)
This article discusses the main reasons for energy transition to RES and examines what is burdening this transition. The main purpose of this article is to overlook the reasons for promotion of renewable energy and main obstacles EU and Ukraine encounter with when heading towards zero-carbon society. The objects of the research were not chosen deliberately: Ukraine is a country which is adopting European aquis communitare and that is why it is extremely important to provide certain comparative research of these formations.